Assessment on the Online Modality Amidst of the Pandemic of Selected Grade 11 Humanities and Social Sciences Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on the Assessment of the respondent in an Online Modality Amidst thepandemic Online Modality study of students in the selected grade 11 students of the BestlinkCollege of the Philippines during the school year 2022-2023. Seven groups of grade 11Humanities and Social Sciences students were selected using the purposive samplingtechnique based on the results of the survey questionnaires. The coronavirus (COVID-19) is apandemic that has had far-reaching effects on nearly every aspect of society, including onlinemodality. School in Bestlink College of the Philippines disease that affects the online modality.Following COVID-19, more advantaged students are attending schools to adopt onlinelearning. Schools in disadvantaged rural areas lack the appropriate digital infrastructurerequired to deliver teaching remotely. Students struggled to stay engaged and connected withtheir teachers and peers online. Distance learning is a solution to continuing the onlinemodality. The lack of network infrastructures and computers.\The researchers conducted online survey questionnaires and answered 50 participants whoexperienced Online Modality. Amidst the Pandemic students, the researchers focused ongrade 11 Humanities and Social Sciences students who experienced the data sought from themeaningful statements and survey questionnaire. The student's meaning was developed andused by the researchers to write the text description of what the students experienced and thedescription of how the students experienced the phenomenon that was created when theywere studying during the pandemic of presenting a consolidated description of the 50participants of seven sections in grade 11 Humanities and Social Sciences students.
Keywords: Education